Diseño y construcción de un módulo didáctico con el plc s7-1200 para la simulación de variación de presión de un fluido - Tigse Soto, Stalin Benito (2017)
A didactic module was designed and built with a programmable logic controller and a touch screen for fluid pressure control, designed to train students by simulating different variables; taking into consideration its construction aspects such as ergonomics and aesthetics that are important at the time of starting the system. The control of the process is carried out in two tanks, a main one that will be the one of discharge of liquid and a secondary one that is going to be that supplies of fluid to the principal, communicated to each other by means of pipes. This system has devices, elements and instruments that perform automatic control of liquid pressure, in addition has a submersible pump installed in the secondary tank that is responsible for providing fluid to the main tank where the liquid level will be monitored directly in their different phases through sensors placed in the tank. The control of the variable liquid pressure (water) was done by a PLC, SIEMENS of the family S7-1200 that based on the signals emitted through sensors, and the program stored in its memory will generate outputs that activate to the contactor Smooth operation of the pump, all this process will be monitored through a KTP-600 man-machine interface (HMI) where orders will be given efficiently, reliably and quickly. Key words: Control, efficiency, pressure, PLC, HMI.